Dispositional Gratitude and Social Comparison Orientation among Social Media Users - Winata, Caroline; Andangsari, Esther Widhi (Bina Nusantara University, 2017)
The study aimed to explore the relationship between dispositional gratitude and social comparison orientation among social media users. The present study used a non-experimental research design with a quantitative approach with survey technique by distributing questionnaires to 296 Bina Nusantara University students aged 18-24 who used social media. The correlation between dispositional gratitude and social comparison orientation was calculated by Spearman correlation technique. The result shows that dispositional gratitude and social comparison orientation have a significant negative correlation.